Musik Melayu dalam Perspektif Industri Budaya - Githa Fitria; Lia Dewi; Marlissa Amelia; Tamara Putri (Journal on Education, 2023)
One of the works of humans is the work of musical art. Music is not just the chanting of notes or sounds that the human sense of hearing enjoys, it can be seen and interpreted as something more profound. This research uses the theory of semiotic analysis of Charles Sanders Pierce, which divides the classification of signs by ground, object, interpretant. This research obtained the results that the development of the times can turn everything authentic into something that can be used as an industry so as to attract capitalists to reap a lot of profits. The positive influence is that Malay music has gone global when previously Malay music was only known around Indonesia. Although undeniable, Malay music today has been influenced by foreign cultures rather than the original culture due to the development of the times and the movement of generations and modernization.